FREQUENCIES OF POLYMORPHISMS IN THE CYTOCHROME’S P450 GENES OF WARFARIN TRANSFORMATION IN A EUROPEAN POPULATION OF EASTERN SIBERIA - T. A. Bairova; E. A. Novikova; F. I. Belyalov; E. A. Shchedreeva; K. D. Ievleva; O. V. Kalyuzhnaya; O. A. Ershova; V. G. Pustozerov; O. A. Kovaleva; I. V. Rasputina; I. A. Noskova; T. V. Batogova; et al. (Acta Biomedica Scientifica)
Background. Genotypes of the cytochrome p450 isoform (CYP2C9 and CYP4F2) determine warfarin dose requirements. Frequencies of risk alleles and genotypes of CYP2C9 and CYP4F2 gene vary in different races and ethnic groups.Aim. This study analyzed the frequencies of *2, *3 alleles of CYP2C9 gene and the 1347 C>T allele of CYP4F2 gene in the Caucasians of Eastern Siberia, and compare with other populations.Materials and methods. Participants were 147 patients (Caucasians): 67 (45.58 %) man and 80 (54.42 %) women), taking warfarin for the prevention of thrombosis with a mean age of 64.74 ± 14.29 years. There were patients with atrial fibrillation – 77 (52.38 %) persons, coronary artery disease – 10 (6.80 %), pulmonary embolism – 5 (3.40 %), 15 (10.20 %) patients after implantation of an mechanical heart valve, etc. The subjects were genotyped for CYP2C9 (*1,*2,*3), and CYP4F2 (1347 C>T) by real-time polymerase chain reaction (RT-PCR) using “Pharmacogenetics Warfarin” reagent kits (DNA technology, Russia).Results. 69.4 % of Caucasians of Eastern Siberia (Russians), have two functional alleles (*1/*1) of CYP2C9 (they’re extensive/normal metabolizers), the number of intermediate metabolizers (*1/*2, *1/*3) was 29.8 % and 0.68 % of slow metabolizers (*3/*3). Homozygous carriers of two non-functional alleles *2 and *3 (*2/*2, *2/*3) were absent. Carriers of one coumarin-resistant Т-allele of CYP4F2 were 57 (38.7 %) respondents, two coumarin-resistant alleles – 10 (6.8 %) respondents.Conclusions. Frequencies of polymorphisms in the Cytochrome’s p450 genes of warfarin transformation in a European population of Eastern Siberia have no differences with other European populations of the world